PENGARUH BUDAYA KERJA, DUKUNGAN ORGANISASI DAN PROFESIONALISME TERHADAP PRODUKTIFITAS KERJA AUDITOR INSPEKTORAT DI PROVINSI ACEH - Marthin Verdinan; Ibrahim Qamarius; Mariyudi Mariyudi (Universitas Malikussaleh, 2022)
This study examined the effect of Work Culture and Organizational Support on Auditor Professionalism and Work Productivity of Inspectorate Auditors in Aceh Province. This study used 126 auditors taken proportionally from 23 regencies and cities in Aceh Province. The analytical tool used was Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) tools. The results indicated that work culture did not influence professionalism of Auditors but significantly influenced the work productivity of Auditors. While the Organizational Support factor significantly influenced the Professionalism and Work Productivity of Auditors. Furthermore, Professionalism significantly influenced the work productivity of Auditors. Meanwhile, in the indirect relationship test, Professionalism did not mediate the relationship between Work Culture and Work Productivity of Auditors. However, Professionalism mediated the relationship between Organizational Support and Work Productivity of Inspectorate Auditors in Aceh Province